2018
DOI: 10.1159/000494651
|View full text |Cite
|
Sign up to set email alerts
|

Nell-1 Enhances Osteogenic Differentiation of Pre-Osteoblasts on Titanium Surfaces via the MAPK-ERK Signaling Pathway

Abstract: Background/Aims: This study aimed to investigate the effect of Nell-1 on the osteogenic behaviors of pre-osteoblasts on titanium (Ti) surfaces and to identify the underlying signaling pathway. Methods: Nell-1 at different concentrations was added to culture medium to stimulate MC3T3-E1 subclone 14 on Ti surfaces. A CCK-8 colorimetric assay was used to detect cell proliferation. Alkaline phosphatase activity (ALP) assay and enzyme-linked immunosorbent assay (ELISA) were used to evaluate ALP activity and the ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 44 publications
(31 reference statements)
1
17
0
Order By: Relevance
“…Therefore, we elucidated the MAPK/ERK signaling pathway underlying the effects of DA on BMSC osteogenic differentiation. Interestingly, the results showed that the D1 receptor agonist selectively activated ERK rather than the JNK and P38 pathways in BMSCs, and different cell types might have influences on this activity [42].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we elucidated the MAPK/ERK signaling pathway underlying the effects of DA on BMSC osteogenic differentiation. Interestingly, the results showed that the D1 receptor agonist selectively activated ERK rather than the JNK and P38 pathways in BMSCs, and different cell types might have influences on this activity [42].…”
Section: Discussionmentioning
confidence: 99%
“…Protein kinase C-binding protein, also known as NELlike protein 1 (NELL1) or Nel-related protein 1, was identified for hand OA in our study. The important role of NELL-1 in driving differentiation and growth of bone and cartilage tissue has been well documented in recent years (25). A recent study showed that adding NELL1 to the human perivascular stem cells (hPSCs) could increase the gene and protein expression of chondrogenic markers, suggesting the role of NELL1 in enhancing and accelerating cartilage repair (26).…”
Section: Discussionmentioning
confidence: 99%
“…SPARC-related modular calcium binding 1 has been revealed to be closely involved in osteogenic differentiation of BMSCs and has the potential to promote bone regeneration in vivo [28]. It has been suggested that the MAPK/ERK signaling pathways may be related to the Nell-1 induced osteogenic differentiation of pre-osteoblasts on titanium surfaces [29]. ERK1/2, p38 MAPK, and JNK osteogenic signaling pathways have been demonstrated to participate in mechanical stress-induced osteoblastic differentiation [30].…”
Section: Discussionmentioning
confidence: 99%